Filling the gap between hypervelocity and low velocity impacts. (May 2020) - Arnold, W.; Hartmann, T.; Rottenkolber, E.
Highlight: Experiments with standard military shaped charges on the hypervelocity range and with elongated STANAG-projectiles on the low velocity range respectively were known and published elsewhere New Experiments with a newly designed Simplified Shaped Charges (SSC) in between in the intermediate velocity range (to close the gap) were conducted and a new initiation model for the whole range from hypervelocity to the low velocity is proposed A Simplified Shaped Charge (SSC) was introduced generating slower and thicker jets closer to STANAG projectiles New ERL-curves were obtained with the new SSC-charges using the same setup as in previous studies The behavior at the root points of the ERL-curves (ERL = VI) with the STANAG-projectiles and the SCCs with thick jets were conclusive and showed good agreement The ERL-curves for the SCC-jets exhibit extensive and ramp-like ERL-slopes, whereas the STANAG-curves have a rather steep slope The " S = constant-rule" is not valid and the stimulus S = v ²∙d is inappropriate for predicting the explosive reaction of a charge on jet / projectile impacts thus requiring a new initiation model A new linear unified initiation model for the whole velocity regime (hyper- to low velocities) is proposed: vcrit = A – B∙d Abstract: During more than one decade of studying initiation phenomenology numerous papers were published by the authors. A multitude of experimental data on hypervelocity impact initiation of plastic bonded high explosive charges by shaped charge jets (SCJ) and some data in the ordnance velocity impact regime obtained with STANAG projectiles and explosively formed projectiles (EFP) were generated. Amongst other findings the results showed that the established assumption that the critical stimulus is constant was wrong and that a new initiation model is needed taking the new results into account. Towards such a new model further investigation was necessary trying to make a link between the initiation phenomenology of shaped charge jet impacts in the hypervelocity regime and of projectile impacts in the lower velocity regime. To bridge the existing data gap a new approach was taken applying newly designed "simplified shaped charges" (SSC). This paper describes the way to this new approach and summarizes the related test results as well as their implications.